Insights into the Synthesis and Bioactivity of Indole-Based Compounds: A Short Review - Bang, Mebantei Janai; Deb, Mohit L. (Current Organic Chemistry, 2026)
Indole derivatives are a significant class of organic compounds with diverse biological activities. They are found in numerous natural products and synthetic drugs, playing a crucial role in medicinal chemistry. In this comprehensive review, we have summarized the synthetic approaches and biological evaluations of a variety of indole derivatives. We analyzed in vitro and in vivo studies assessing the bioactivity of indole derivatives, focusing on structure-activity relationships. The versatility and efficacy of indole-based compounds hold great potential for advancing medical therapies, particularly in the fields of cancer treatment, infectious diseases, and inflammatory disorders. This concise review aims to inspire further research on indole-based compounds for drug development.
Keywords: melatonin